1990
DOI: 10.1007/978-1-4684-5847-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Study on Vitamin B12 Levels in Serum and Cerebrospinal Fluid of Patients with Alzheimer’s Disease

Abstract: Vitamin B12 levels in the serum and the cerebrospinal fluid (CSF) were compared between patients with Alzheimer's disease (AD) and senile dementia of Alzheimer's type (SDAT) (AD group) and patients with multi‐infarct dementia (MID group). The B12 levels in the serum and the CSF were 742 ± 359 pg/ml and 28 ± 7 pg/ml (mean ± SD), respectively, in the AD group, and 962 ± 254 pg/ml and 50 ± 26 pg/ml, respectively, in the MID group. CSF B12 levels were significantly lower in the AD group than in the MID group, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Concentrations of serum cobalamin did not differ between AD patients and control subjects (70). In contrast, CSF concentrations of cobalamin were significantly lower in AD patients when compared to age-matched controls (70). Therefore, it seems that CSF cobalamin becomes depleted at a relatively early stage of cobalamin deficiency that probably may not be reflected by total serum cobalamin.…”
Section: Brain and Csf Cobalaminmentioning
confidence: 89%
See 1 more Smart Citation
“…Concentrations of serum cobalamin did not differ between AD patients and control subjects (70). In contrast, CSF concentrations of cobalamin were significantly lower in AD patients when compared to age-matched controls (70). Therefore, it seems that CSF cobalamin becomes depleted at a relatively early stage of cobalamin deficiency that probably may not be reflected by total serum cobalamin.…”
Section: Brain and Csf Cobalaminmentioning
confidence: 89%
“…HoloTC is the active part of cobalamin and the one that can be internalized via a specific receptor. Concentrations of serum cobalamin did not differ between AD patients and control subjects (70). In contrast, CSF concentrations of cobalamin were significantly lower in AD patients when compared to age-matched controls (70).…”
Section: Brain and Csf Cobalaminmentioning
confidence: 90%
“…Discouraging results have been obtained also in clinical trials with Vitamin C (for which almost same antioxidant principles could apply) and/or vitamin E [44]. Although another attractive hypothesis to be mentioned is the ''cobalaminergic'' [45] elaborated by the low CSF and serum vitamin B12 levels evidences in Alzheimer's patients [46,47], vitamin B12 is biochemically, and nutritionally intimately related to folic acid [19], for which a specific chapter should be held. In fact, folates are essential for central nervous system development, and insufficient folate activity at the moment of conception and during early pregnancy can result in congenital neural tube defects.…”
Section: Disease Mechanism(s)mentioning
confidence: 99%
“…The levels of transthyretin, vitamin B12, vitamin E and folate have been reported to be lowered in the CSF of AD patients [9,11,17,18,22]. Morphological studies further demonstrated CP fibrosis in deceased AD patients [10].…”
Section: Introductionmentioning
confidence: 99%